Aporia : [(Ancient Greek ἀπορία : “impasse, difficulty of passing, lack of resources, puzzlement”) denotes in philosophy a philosophical puzzle or state of puzzlement and in rhetoric a rhetorically useful expression of doubt. - Wikipedia ] : an exegesis presented in partial fulfilment of the requirements for the degree of Masters of Fine Arts at Massey University, Wellington, New Zealand - Royal, Nigel (Massey University, 2014)
This exegesis is the result of my investigation into self-reference and paradox to reflect the difficulties I experience with dyslexia, in it I am describing and manifesting my own doubts and anxiety when confronted with the task of producing this text based document. A circular discussion results, because to understand the problem one has to understand one’s own thinking, this is the loop that the dyslexic is stuck within when confronted by the medium of written language. In it I question the notion of ‘self’ said to be socially constructed through language as a way to manifest ‘affect’ within video installation space. What I have written about is the paradox of self-reference that exists within language that causes confusion between description of the world and the effect/affect of the infolding and out-folding of embodied experiences in space. When in the proximity of other bodies, objects, events, images and things.
Keywords: Video art installations; Words in art; Dyslexia